Implementasi Nodemcu ESP8266 Untuk Penghematan Energi Listrik Studi Kasus Di Kontrakan Dr. Alik - U. Darmanto Soer (Teknik Informatika, Universitas Pelita Bangsa, 2020)
The widely proposed technological model of increasing savings in electrical energy at overuse is an interesting topic for many studies because of the effects of excess electricity usage itself. And the technology model applied is a smart home for this problem, using a microcontroller for automatic devices using a motion sensor, namely a PIR (passive infrared) sensor for controlling lights in a room. With this method can reduce and save the cost of using lamps in vain from forgetting to turn off the lights. And the device will turn on the light when it detects movement and will turn off the light when it doesn't detect any movement. by using the Kwh cost calculation algorithm, we will find out the costs to be paid from the number of times the lights are on. The test results show that this device can work well according to the design with a success rate of 100%.. Keywords: NodeMCU, Smart Home, Remote Relay, Sensor PIR